113 Ketogenic diet services at children's hospital across the united kingdom. (22nd November 2019) - Simpson, Zoe; Eltze, Christin; Smith, Hannah; Bor, Bahee Van de; Urban, Victoria; McCullough, Fiona
Abstract : Background: Ketogenic diets (KD) are a high fat, low carbohydrate and sufficient protein diet used as a treatment option for pharmacoresistant epilepsy. 1 There is no evidence to support the most efficient and effective way to manage a KD service. We surveyed KD services with the aim to compare service organisation, highlighting differences. Methods: A questionnaire was emailed to 14 established KD services in England. Information was obtained through 5 questions focusing on clinic structure, healthcare professionals (HCP) involved and patient numbers. Data was input in to Microsoft Excel and analysed. No ethical approval was required. Results: Seven centres responded. The KD service caseloads varied from 25 – 100 patients (mean = 55), with a total capacity for 336 patients across all services. Number of patients per WTE dietitian ranged from 19 – 33. The total face-to-face clinic time provided per patient varied from 5-7 hours from initial assessment to the end of the two-year treatment time, with a mean of 5.9 hours. Follow up was usually provided at 3 and 6 months initially and 6-12 monthly subsequently. Discussion: The results highlight that KD care provision was variable across all centres. Although the clinic follow-up time points were similar to that recommended by the international consensus (1) there was variation in face-to-face contact time per patient. It would be important to identify the impact of the additional face-to-face time per patient on outcomes including seizures, safety and retention. The differences between patient numbers and dietetic time may be due to funding and the patient-care pathway. Conclusion: Ongoing review and assessment of current practice across UK centres is important and future surveys should include outcome data. Further research is required and the generation of national consensus standards for a KD pathway would help to achieve equitable and effective KD provision.